RETRACTED ARTICLE: Improved AODV Based on TOPSIS and Fuzzy Algorithms in Vehicular Ad-hoc Networks - Amiri, Esmaeil; Hooshmand, Reza (Wireless personal communications, 2020)
The ad-hoc on-demand distance vector (AODV) routing protocol is one of the most widely used routing protocols in VANETs. The AODV finds the shortest path that is not desirable in networks with high mobility. In addition, in the AODV, path request messages are broadcasted by the source and middle vehicles, which increases the routing overhead. However, in this paper, each vehicle selects the most reliable neighbors in order to send path request. This selection is based on the technique for order of preference by similarity to ideal solution algorithm. As a result, the destination vehicle receives the most reliable paths and uses the fuzzy algorithm to select the best route from the perspective of failure among all received routes. Simulation results show that the proposed method has lower end-to-end latency and higher throughput than the AODV.